Rancang Bangun Kunci Pintu Dengan Sensor RFID Dan Sensor DTH 11 Berbasis Arduino pada Sekolah Tinggi Ilmu Kesehatan Salsabila Serang - Sutanto Sutanto; Dwi Tirto (LPPM Unbaja, 2019)
In the current era of globalization in the field of technology is very rapid, and has increased to human life. This we can see with what can from technology. Use technology that we can use to use electronic devices that can be used to help with day-to-day work. Likewise with today's environment many things are related to security or security as it happens in office or office that needs a lot of information and can not be done with easy access. In the future, we need a tool to access it using RFID (Radio Frequency Identification) and a card for entrance access on the door will boost the spirit at that time. With automatic door locks using RFID and relays that connect RFID modules with door locks and accessed with arduino, and provide sms notifications for security if outside happens to increase the temperature and humidity to do more and better to improve, which is then supported by history access of each RFID tag card which of every RFID tagging card will be stored in the data base.